UPAYA PENCEGAHAN CEDERA OLAHRAGA SEBELUM DAN SELAMA PERTANDINGAN PADA UKM OLAHRAGA UMPP TAHUN AKADEMIK 2019/2020 - -, mega (STKIP Muhammadiyah Kuningan Secretariat Jurnal Muhammadiyah Untuk Olahraga Indonesia. Building A106 Street of Murtasiah Soepomo No 28b, 45511 Kuningan - West Java Telephone : 0232-874085 Homepage : E-mail:, 2021)
Every person when exercising is always faced with the possibility of an injury and this injury can interfere with daily activities and can even be so fatal that he cannot perform activities at all for weeks. The cause of sports injuries is trauma (forced ruda) directly (hitting soft tissues, namely: skin, muscles, tendons and ligaments) or indirectly (hitting hard tissues, namely bones). This trauma can occur due to 2 factors, namely the Overuse factor (overuse syndrome) and environmental factors (temperature, weather, altitude, and depth). In general, many sports injuries are caused by overuse factors. According to Wibowo (1995) in Jamal (2009: 1)